Gastric and small intestinal traditional serrated adenomas: a detailed morphologic and immunohistochemical analysis - Saba Kiremitçi; Cevriye Cansız Ersöz; Berna Savaş; Arzu Ensari (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Traditional serrated adenomas (TSAs), despite their low incidence in colorectum, may originate in other parts of the gastrointestinal (GI) tract, including stomach and small intestine. Malignant transformation for upper GI TSAs has recently been reported in the literature. Here, we present a series of gastric and small intestinal TSAs with the aim to characterize their morphologic and immunophenotypic features as well as their neoplastic potential in a compartmental manner using digitalized images.Materials and Methods: The study comprised 12 GI polyps with TSA features—5 gastric and 7 small intestinal. The extent of the characteristic features of TSA, including eosinophilic cells, ectopic crypt foci (ECF), slit-like serration, foveolar epithelium, goblet cells, together with dysplastic/carcinomatous foci were assessed on digitalized H&E images and were used as reference for immunohistochemical analysis.Results: All polyps in the cohort contained eosinophilic cells as the most extensive morphologic feature followed by ECF and slit-like serration in decreasing order. Serrated dysplasia was more common in gastric polyps, which more frequently showed neoplastic progression compared with the intestinal ones. CK20 was the most widely expressed marker with a preference to eosinophilic cells while ECFs were mostly negative. Ki67 showed the opposite pattern of CK20. MUC6 and MUC2 were selectively expressed in the basal zone and goblet cells, respectively.Conclusion: Our results showed that the presence of eosinophilic cells with pencillate nuclei commonly accompanied by ECF and slit-like serration are the defining features of gastric and small intestinal TSAs. They frequently harbor neoplastic foci, particularly in gastric location where serrated dysplasia seems to be more common.Cite this article as: Kiremitci S, Cansız Ersoz C, Savaş B, Ensari A. Gastric and small intestinal traditional serrated adenomas: a detailed morphologic and immunohistochemical analysis. Turk J Gastroenterol 2020; 31(6): 441-50.